African solutions to African problems and the Ebola virus disease in Nigeria. Issue 2 (17th February 2016) - Umukoro, Nathaniel
ABSTRACT: Africa grapples with the world's most serious public health crisis, but this article shows that there are public health solutions that work in the African setting. When the Ebola virus disease outbreak was announced in Nigeria in July 2014, some public health specialists worried that an apocalyptic outbreak would sweep through the vast slums of Lagos. The words "Ebola" and "Lagos" in the same sentence were viewed as a dangerous combination, due to the large population of Lagos and the inefficient health care system in the city. Contrary to this view, the outbreak of Ebola virus disease was successfully contained in Nigeria. This article focuses on the factors that were responsible for this success. It examines strategies developed within Nigeria that help to ensure the successful containment of the disease. The paper identifies lessons that can be learnt by other countries from the Nigerian experience.